The role of online tourism education and its impact on student wellbeing during a ‘COVID-pause’ (Journal of Applied Learning and Teaching, 2023)
The COVID-19 pandemic created an extremely challenging landscape for the tourism and hospitality industry, particularly in terms of the wellbeing of those employed in the sector. In mid-2020, in response to the pandemic, the University of Tasmania, in conjunction with the Tourism Industry Council of Tasmania, designed a fee-free Graduate Certificate of Tourism, Environmental and Cultural Heritage for Tasmanian residents employed in the tourism sector who were impacted by COVID-19. The course was designed to upskill participants, but as the course progressed, anecdotal evidence emerged about the wellbeing side-benefits of this online educational offering.As a result, an empirical study was conducted as it was not clear from previous research whether online education could contribute towards psychological wellbeing during a pandemic. A web-based survey and focus groups were designed to collect data. The findings revealed the extent that online delivery in tourism higher education can contribute towards wellbeing during a prolonged crisis event. It revealed that the free education attracted students who would not normally attend university. As a result, they felt a great sense of achievement and, ultimately, wellbeing during and following the completion of the course. The findings also revealed that the hybrid online model employed for this teaching model generated a sense of community and wellbeing.